2022
DOI: 10.1111/1541-4337.13092
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of furan in foods: From dietary exposures and in vivo metabolism to mitigation measures

Abstract: Furan is a thermal food processing contaminant that is ubiquitous in various food products such as coffee, canned and jarred foods, and cereals. A comprehensive summary of research progress on furan is presented in this review, including discussion of (i) formation pathways, (ii) occurrence and dietary exposures, (iii) analytical techniques, (iv) toxicities, (v) metabolism and metabolites, (vi) risk assessment, (vii) potential biomarkers, and (viii) mitigation measures. Dietary exposure to furan varies among d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 185 publications
(298 reference statements)
0
3
0
Order By: Relevance
“…Then, 600 μL of the filtrate was transferred to 5 mm NMR tubes for NMR analysis. 1 H and 13 C NMR distortionless enhancement by polarization transfer (DEPT) and 1 H− 1 H correlation spectroscopy (COSY) spectra were recorded by using an Agilent DD2 600 MHz NMR spectrometer equipped with a cryoprobe incorporating a z-axis gradient.…”
Section: Determination Of Furan By Hs-gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 600 μL of the filtrate was transferred to 5 mm NMR tubes for NMR analysis. 1 H and 13 C NMR distortionless enhancement by polarization transfer (DEPT) and 1 H− 1 H correlation spectroscopy (COSY) spectra were recorded by using an Agilent DD2 600 MHz NMR spectrometer equipped with a cryoprobe incorporating a z-axis gradient.…”
Section: Determination Of Furan By Hs-gc-msmentioning
confidence: 99%
“…Furan (C 4 H 4 O) is a heterocyclic and highly volatile compound with a low boiling point of 31 °C, which occurred in a wide range of thermally processed (baking, roasting, pasteurizing, cooking, and sterilizing) foods and beverages, especially in roasted coffee, canned or jarred food. 1 Furan has been proven to be carcinogenic in animal models and classified as "possibly carcinogenic to humans" (group 2B) by the International Agency for Research on Cancer (IARC). Based on the rodent liver tumor incidence data, the joint FAO/WHO expert committee on food additives (JEFCA) concluded that current exposure to furan from foods indicates a human health concern.…”
Section: Introductionmentioning
confidence: 99%
“…Poremećaj je u većini slučajeva prolazne prirode i primarno pogađa nasledno sklonu decu, najčešće odojčad, a posebno onu u prvom polugođu po rođenju i na veštačkoj ishrani ili dohrani [6][7][8] . Pored nasleđene predispozicije i razvojne nezrelosti gastrointestinalne antigenske barijere i imunoregulacije, naročito u stanju urođenog deficita imunoglobulina A (IgA), pojavi alergije na hranu u najranijem uzrastu doprinose nedostatak vitamina D i omega-3 višestruko nezasićenih masnih kiselina, kako pre rođenja, tako i nakon toga, prekomeran unos omega-6 nezasićenih masnih kiselina, crevna disbioza kao posledica rođenja carskim rezom i antibiotske terapije majke pri kraju trudnoće ili deteta u prvim postnatalnim nedeljama, rana dohrana ili veštačka ishrana, prerano uvođenje nemlečne hrane i ponavljane crevne infekcije 2,7,[9][10][11] . Senzibilizacija na proteine hrane, nekad i haptene, najčešće nastaje direktnom ekspozicijom, ali je moguća i putem majčinog mleka, pa čak i transplacentarno 6,12,13 .…”
Section: Uvodunclassified
“…However, an analysis of the literature showed an almost complete lack of data about studies on the biological activity of magnesium carboxylate complexes with N-donor ligands [21][22][23][24]. 2-Furoic acid was chosen as the biological active organic component [25][26][27], the pharmacophore fragment of which is the founder of a whole group of antimicrobial drugs such as furazolidone, furadonin, enterofuril, etc. [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%